[OP.2B.08] ETIOLOGY OF RENAL INFARCTIONS: A RETROSPECTIVE ANALYSIS OF 229 CONSECUTIVE CASES ADMITTED TO A SINGLE TERTIARY CENTER OVER 15 YEARS. (September 2016) - Faucon, A.; Bobrie, G.; Jannot, A.S.; Azarine, A.; Amar, L.; Plouin, P.F.; Azizi, M.
Abstract : Objective: Renal infarction (RI) is a rare disease (0.004% of patients admitted to emergency units), due to a disruption of renal blood flow of the main ipsilateral renal artery (RA) or of one of its segmental branches due to either a local in-situ or a general mechanism. The local mechanism includes RA occlusion, dissection, aneurysm or stenosis which 1) may lead to in-situ RA thrombosis or renal emboli and 2) can be due to various etiologies including atherosclerosis disease (ASD), fibromuscular dysplasia (FMD), dissecting hematoma (DH), extension of an aortic dissection (AoD) to the RA, miscellaneous arterial disease (AD), iatrogenic post-RA catheterization/surgery complication (IC) or post-renal trauma complication (T). The general mechanism includes thromboembolic disease (TED) due to arrhythmia, aortic thromboembolism, or a hypercoagulable state. The aim of this study is to analyze the various RI causes. Design and method: Patients with RI admitted consecutively to our tertiary hospital center between 07/2000 and 06/2015 were retrospectively identified from the weekly reports of our multidisciplinary rounds. Main clinical and biological characteristics of the patients were extracted from our clinical data warehouse. All identified patients had renal CT-angiogram (CTA) which was reviewed by two readers blind to the first radiological report to confirm RI diagnosis and assess its underlying mechanism/etiology. In case of discrepancy between the independent CTA reading and the initial CTA or multidisciplinary meeting report (n = 41), the final diagnosis was made by a vascular radiologist on a third independent reading. Results: We identified a total of 278 patients of whom 49 were excluded and the 229 remaining had confirmed RI. The 2 most frequent mechanisms of RI were RA occlusions (48%) and dissections (36%) (table). RA occlusions were mainly due to ASD. RA dissections mainly related to DH (43%) and FMD (20%). 19% of RI were due to a complication of an endovascular or surgical procedure. Figure. No caption available. Conclusions: In this large case series, RI was predominantly due to in-situ mechanisms mainly related to RA occlusion or dissection. RA occlusions were more frequently associated with ASD whereas RA dissections were mainly related to DH and FMD.